A Study on the Economy of Sacle in Chinese Mutual Fund Industry with Forward Demeaning Method - Li, Mingchun (Journal of Global Economy, Business and Finance, 2025)
China’s securities investment fund market has experienced rapid expansion in the past two decades, and the impact of fund size expansion on fund performance presents a complex relationship. On the one hand, the theory of economies of scale indicates that an increase in scale may bring cost savings and better resource allocation; on the other hand, actual research shows that as fund size increases, fund performance tends to decline, and there is a phenomenon of diminishing returns to scale. Based on the forward mean method, this paper takes China’s actively managed equity and equity-oriented hybrid funds from 2005 to 2023 as samples to empirically test the relationship between fund size and performance. The study found that there is a significant economy of scale effect in China’s fund market: for every 1% increase in fund size, the risk-adjusted total return in the next quarter will increase by about 0.258% (equivalent to 1.03% annualized), which is in sharp contrast to the traditional “diseconomies of scale” theory and the experience of the US market. The study further pointed out that factors such as the low efficiency of China’s capital market, abundant investment opportunities, and intensified fee competition provide unique conditions for economies of scale. The research conclusions provide a new perspective for understanding the characteristics of the emerging market fund industry and verify the effectiveness of the forward mean method in solving the endogeneity problem.